Prevalence, predictors, and mortality of Super-Fontan patients in a single-centre nationwide cohort - Illinger, Vojtěch; Slabý, Kryštof; Radvanský, Jiří; Jičínská, Denisa; Materna, Ondřej (Cardiology in the young, 2025)
AIMS: To evaluate the prevalence, long-term mortality, and clinical characteristics in total cavopulmonary connection patients with excellent functional outcomes. METHODS AND RESULTS: A retrospective study of cardiopulmonary exercise test results in 288 patients after total cavopulmonary connection from a single-centre nationwide database. A subgroup of 88 (30.6%) patients (45 women; 51.1%), at a median age 13.0 [interquartile range 11.0; 18.0] years achieved ≥80% of predicted VO2peak value (Super-Fontan phenotype). Survival free from death or heart transplantation 20 years after surgery was 100.0% in the Super-Fontan group versus 94.0% in the rest of the cohort (p = 0.04). Super-Fontan patients were younger, had lower body mass index, lower regurgitant fraction on atrioventricular valve, and larger preoperative McGoon ratio than the rest of the cohort (p = 0.002, p < 0.0001, p = 0.004, and p = 0.04, respectively). Females and tricuspid atresia patients were significantly more prevalent in the Super-Fontan group than in the rest of the cohort (p = 0.02 for both). There was no difference regarding systemic ventricle morphology, fenestration presence, or ejection fraction of systemic ventricle between the Super-Fontan group and the rest of the total cavopulmonary connection cohort (p = 0.06, p = 0.09, and p = 0.64, respectively). CONCLUSIONS: The subgroup of Super-Fontan patients has unique clinical characteristics when compared to the rest of the total cavopulmonary connection nationwide cohort. Besides superior VO2peak results, Super-Fontan patients tend to have lower long-term mortality, body mass index, and atrioventricular valve, greater preoperative pulmonary dimensions, and a higher prevalence of females and tricuspid atresia patients. There was no variance in morphology of the systemic ventricle, or presence of fenestration.
Keywords: Super-Fontan; zátěžový test; Humans; dítě; prevalence; Child; Female; mladý dospělý; Exercise tolerance; lidé; Exercise Test; vrozené srdeční vady; total cavopulmonary connection; Survival Rate; Follow-Up Studies; ženské pohlaví; Male; peak oxygen consumption; Retrospective Studies; Adolescent; Fontan Procedure; Heart Ventricles; Young Adult; Prevalence; Fontan circulation; retrospektivní studie; míra přežití; mužské pohlaví; srdeční komory; následné studie; mladiství; Fontanova operace; Heart Defects, Congenital